Об ареале кавказской крестовки Pelodytes caucasicus (Amphibia, Pelobatidae) - Голубев, Н.С. (Вестник зоологии, 1980)
Pelodytes caucasicus B o u l e n g e r is distributed in the forest zone of the North-Western Caucasus and Transcaucasian area. Its distribution is influenced by the locality relief, temperature, humidity. Anthropogenic factor (forest felling) results in the reduction of the P. caucasicus area of distribution.